2011
DOI: 10.21236/ada581257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soot Structure on Soot Oxidation Kinetics

Abstract: The public reporting burden for this collection of information is es1imated to average 1 hour per response, including the time for reviewing instructions, searching exis1ing data sources, ga1hering and maintaining the data needed, and completing and review ing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of This project focused on the mechanisms of soot oxidation by 02. A two-stage burner was used. Soot was generated for ethylene, JP-8 surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The fringes’ median size ranges from 0.9–1.2 nm, corresponding to aromatics with 14–22 aromatic rings (assuming a circular pericondensed aromatic). The results for the lowest height above the burner (10 mm) provide insight into the species present at nuclei formation; there, L = 0.9–1.05 nm, corresponding to a size of 15 aromatic rings, consistent with optical band gap measurements and mass spectrometry …”
Section: Results and Discussionsupporting
confidence: 66%
“…The fringes’ median size ranges from 0.9–1.2 nm, corresponding to aromatics with 14–22 aromatic rings (assuming a circular pericondensed aromatic). The results for the lowest height above the burner (10 mm) provide insight into the species present at nuclei formation; there, L = 0.9–1.05 nm, corresponding to a size of 15 aromatic rings, consistent with optical band gap measurements and mass spectrometry …”
Section: Results and Discussionsupporting
confidence: 66%
“…Numerical modeling is a promising tool to reach this goal; nevertheless, the main mechanisms involved in the soot formation (mainly surface growth and oxidation) need to be better understood (Mueller et al 2011). To reach this goal, many studies have been performed in flames for soot characterization under the oxidation process by ex-situ techniques (Ghiassi et al 2016;Jung et al 2004;Kim et al 2005;Lee et al 1962;Lighty et al 2011;Ma et al 2013;Puri et al 1994) or in-situ optical techniques (Garo et al 1988;Garo et al 1990;Neoh et al 1985;Xu et al 2003), the latter generally based on laser light extinction, scattering and the depolarization ratio. Most of these studies, however, cannot isolate oxidation from surface growth mechanisms occurring within sooting flames.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting way to overcome this drawback and to focus on the oxidation process is to inject previously produced soot particles into a non-sooting flame (I.e. a "two stage burner") as previously done by Neoh et al (1985), Lighty et al (2011), Echavarria et al (2011) and very recently by Ghiassi et al (2016) and Sirignano et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Three lines denoted as N–S-C are the soot oxidation rates at different O 2 partial pressures proposed by N–S-C. 3 Song et al 35 investigated oxidation of diesel exhaust soot using a flat flame burner and found the oxidation rates fallen in domains predicted by the N–S-C formula in a temperature range between 1530 and 1820 K. The hollow circles are the plots from Fenimore and Jones 36 experiment conducted in a temperature range between 1530 and 1890 K. They suggested the importance of the oxidation by OH even in this low-temperature range. Lighty et al 37 also urged that soot oxidation by O 2 is predominant under lean conditions while oxidation by OH plays significant contribution to soot burnout in fuel-rich cases under similar temperature range.…”
Section: Surface-specific Soot Oxidation Ratementioning
confidence: 99%